CYBERBULLYING IN NIGERIA - CHIOMA CHRISTIANA AKUNEME; KINGSLEY CHINAZA NWOSU (Social Sciences and Education Research Review)
This systematic research synthesis sought to investigate cyberbullying in Nigeria in relation to its concept, prevalence, negative outcomes and intervention. To carry out this review, a systematic search using variations of cyberbullying search terms was performed using some inclusion and exclusion criteria. Results revealed that though some Nigerian researchers have made commendable efforts to investigate cyberbullying among Nigerian youths, the shortcomings in their operational definitions of cyberbullying, may lead to the use of cyber aggression interchangeably with cyberbullying. Results also revealed that in contrast to most countries, no intervention program has been designed to address cyberbullying in Nigeria. This finding has implications for researchers in Nigeria. To prevent cyberbullying victims from suffering the long-term or short-term negative effects associated with cyberbullying, researchers in Nigeria are called upon to develop intervention programs that will serve as evidence-based treatment strategies for the victims of cyberbullying in Nigeria. Future researchers in Nigeria should also take into consideration the 3 important criteria for defining cyberbullying and as well extend their investigation beyond university students.